Зарубіжний досвід протидії насильству в сім’ї та можливості його використання в Україні - Легенька, М. М.; Lehenka, M. M. (Право і безпека. – 2017. – № 4 (67). – С.111-116, 2017)
Обґрунтовано актуальність вивчення та врахування в нормотворчій діяльності міжнародних стандартів протидії домашньому насильству. Проаналізовано модельне законодавство ООН про домашнє насильство та перспективи впровадження його норм у вітчизняну практику. Узагальнено досвід законодавчого забезпечення боротьби з домашнім насильством у країнах Європи з точки зору можливостей його використання в Україні.

The author has substantiated the relevance of studying and taking into account in law-making activity of international standards of counteracting domestic violence. At the same time, the strengthening of the fight against domestic violence has been attributed to the most important features of progress in domestic jurisprudence. The UN model law on domestic violence has been analyzed. It has been noted that the analyzed model law defined the concept of domestic violence and formulated the requirements for law enforcement officers, prosecutors and courts. It has been emphasized that this law established compulsory actions of law enforcement officers in case of reacting to the fact of domestic violence. Particular attention has been paid to the provisions focused on protective orders and regulations. The concept of emergency temporary restraining order, which prohibits further domestic violence, has been revealed. The complex of measures of social, moral and ethical, psychological and pedagogical nature aimed at ensuring counteraction to domestic violence and provided by the model law has been characterized. The ways of implementing the norms of the model law into the national practice have been analyzed; and the expected high efficiency of such an implementation has been noted. The author has analyzed the regulatory and organizational experience of combating domestic violence accumulated in advanced European countries. The relevant legal regulations that are in force in these countries, with reference to their effectiveness have been characterized. It has been emphasized that the experience of legal counteraction to domestic violence in European countries and the provisions of the UN model law on combating these types of violence can serve as a serious legal basis for the development of domestic law and law-enforcement practice.

Обоснована актуальность изучения и использования в нормотворчестве международных стандартов противодействия домашнему насилию. Проанализировано модельное законодательство ООН о домашнем насилии и раскрыты перспективы внедрения его норм в отечественную практику. Обобщён опыт законодательного обеспечения борьбы с домашним насилием в странах Европы и мира с точки зрения возможностей его использования в Украине.
International experience in combating domestic violence and the possibilities of its implementation in Ukraine
Зарубежный опыт противодействия насилию в семье и возможности его использования в Украине
Легенька, М. М. Зарубіжний досвід протидії насильству в сім’ї та можливості його використання в Україні / М. М. Легенька // Право і безпека. – 2017. – № 4 (67). – С.111-116.
Lehenka, M.M. (2017), “International experience in combating domestic violence and the possibilities of its implementation in Ukraine” [“Zarubizhnyi dosvid protydii nasylstvu v simi ta mozhlyvosti yoho vykorystannia v Ukraini”], Pravo i Bezpeka, No. 4, pp. 111–116.
Keywords: Міжнародне право .International Law. Международное право; Наукові публікації. Scientific publications. Научные публикации; домашнє насильство; запобігання домашньому насильству; протидія домашньому насильству; міжнародні нормативно-правові стандарти; законотворчість; міжнародний досвід; захисний припис; предотвращение домашнего насилия; противодействие домашнему насилию; международные нормативно-правовые стандарты; международный опыт; защитное предписание; домашнее насилие; насильство в сім`ї; насилие в семье; prevention to domestic violence; domestic violence; domestic violence prevention; counteraction to domestic violence; international regulatory standards; law-making; international experience; protective order